Enhanced RAGE Expression and Excess Reactive-Oxygen Species Production Mediates Rho Kinase-Dependent Detrusor Overactivity After Methylglyoxal Exposure - Oliveira, Akila L.; Medeiros, Matheus L.; de Oliveira, Mariana G.; Teixeira, Caio Jordão; Mónica, Fabíola Z.; Antunes, Edson (Frontiers in Physiology, 2022)
Methylglyoxal (MGO) is a highly reactive dicarbonyl compound implicated in diabetes-associated diseases. In vascular tissues, MGO induces the formation of advanced glycation end products (AGEs) that bounds its receptor RAGE, initiating the downstream tissue injury. Outside the cardiovascular system, MGO intake produces mouse voiding dysfunction and bladder overactivity. We have sought that MGO-induced bladder overactivity is due to activation of AGE-RAGE-reactive-oxygen species (ROS) signaling cascade, leading to Rho kinase activation. Therefore, female mice received 0.5% MGO orally for 12 weeks, after which in vitro bladder contractions were evaluated in the presence or not of superoxide dismutase (PEG-SOD) or the Rho kinase inhibitor Y27632. Treatment with MGO significantly elevated the serum levels of MGO and fluorescent AGEs, as well as the RAGE immunostaining in the urothelium, detrusor, and vascular endothelium. RAGE mRNA expression in the bladder was also higher in the MGO group. Methylglyoxal significantly increased the ROS production in both urothelium and detrusor smooth muscle, with the increases in detrusor markedly higher than urothelium. The bladder activity of superoxide dismutase (SOD) was significantly reduced in the MGO group. Gene expressions of L-type Ca2+ channels, RhoA, ROCK-1, and ROCK-2 in bladder tissues were significantly elevated in the MGO group. Increased bladder contractions to electrical-field stimulation, carbachol α,β-methylene ATP, and extracellular Ca2+ were observed after MGO exposure, which was significantly reduced by prior incubation with either PEG-SOD or Y27632. Overall, our data indicate serum MGO accumulation elevates the AGEs levels and activates the RAGE-ROS signaling leading to Rho kinase-induced muscle sensitization, ultimately leading to detrusor overactivity.